Hubungan Kepemimpinan Kepala Sekolah dan Sikap Guru Terhadap Pekerjaan dengan Kompetensi Profesional Guru - Sonedi Sonedi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The aim of this study; 1). to know the relationship of the principal leadership to the teacher’s professional competence at Junior High School of Palangka Raya city; 2). to know the relationship of teachers’ attitudes to their work, and 3). to know the relationship of principal leadership, teachers’ attitudes to their work with the teachers’ professional competence at the private Junior High School of Palangka Raya city. These results showed that: 1) there is a significant relationship with the leadership of the principal with the economic teachers’ professional competence at the private Junior High School of Palangka Raya city. It means that the higher the level of the principal leadership, it will be followed by the higher of the professional competence of the teachers. Conversely, the lower of the leadership of the principal, the professional competence of the teachers will be lower too; 2) there is a significant relationship of the teachers’ attitude to their work with the economic teachers’ professional competence at private Junior High Shool in Palangka Raya city. It means that the higher of positive teachers’ attitude to work, the professional competency of the teachers will be higher, and vice versa; 3) there is a significant relationship of the principal leadership and teachers’ attitudes to their work with economic teachers’ professional competence at the private Junior High School in Palangka Raya city.